(untitled) (Edad Media. Revista de Historia, 2022)
By examining the late medieval Portughese curial nobility, this article aims to determine the ways in which marriage contributed to provide stability to aristocracy as a minoritarian, endogamous and dominant group. The documentation preserved in public and noble houses archives facilitated the creation of a corpus of marriage contracts, family partitions and wills. This corpus allows us to consider and examine material aspects, familial strategies, and other marital social interactions. The main argument that this article proposes is that marriage was an essential mechanism through which strong and dense social relations were built. This case study demonstrates a pattern of social endogamy, organised by the relations structured around the Portuguese royal court, intertwined with distant consanguineous and close affinity marriages.